Overview of DNA Self-Assembling: Progresses in Biomedical Applications - Andreia F. Jorge; Ramon Eritja (MDPI AG, 2018)
Molecular self-assembling is ubiquitous in nature providing structural and functional machinery for the cells. In recent decades, material science has been inspired by the nature’s assembly principles to create artificially higher-order structures customized with therapeutic and targeting molecules, organic and inorganic fluorescent probes that have opened new perspectives for biomedical applications. Among these novel man-made materials, DNA nanostructures hold great promise for the modular assembly of biocompatible molecules at the nanoscale of multiple shapes and sizes, designed via molecular programming languages. Herein, we summarize the recent advances made in the designing of DNA nanostructures with special emphasis on their application in biomedical research as imaging and diagnostic platforms, drug, gene, and protein vehicles, as well as theranostic agents that are meant to operate in-cell and in-vivo.